PENGARUH VARIASI MEDIA PELAPIS TERHADAP PEMOTONGAN AKRILIK TRANSPARAN DENGAN PROCUT DIODE 15 WATT - Della Dwi Friatinia; Sairul Effendi; Almadora Anwar Sani (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
Laser cutting machines are widely utilized in various industries for cutting diverse materials. One commonly used material is acrylic, which is typically processed using CO2 laser cutting machines. However, such machines have the drawback of being relatively expensive. As an alternative, diode laser cutting machines offer a more cost-effective solution, although their effectiveness on acrylic, particularly transparent acrylic, remains to be thoroughly validated. Diode laser modules are known to cut materials such as paper, wood, bamboo, leather, and plastics. Preliminary tests indicate that the laser beam does not produce cutting effects on transparent acrylic due to its ability to pass through the material. This study aims to evaluate the effectiveness of coating methods in cutting transparent acrylic using diode lasers and to identify the optimal parameters. Three types of coating media were used: paper, adhesive tape, and black MDF board. The results show that transparent acrylic can be successfully cut using a paper coating, with the optimal parameters being a power intensity of 90%, a cutting speed of 6 mm/min, and two repetitions. These findings provide an economical solution for cutting transparent acrylic using diode laser cutting machines.